Penalaran TaâLÃ®ilÃ® dalam Hukum Islam: Telaah Corak Penalaran Hukum Islam dalam Upaya Penerapan MaqÃ¢Åid al-SharÃ®âah - Aibak, Kutbuddin (Program Pascasarjana UIN Sunan Ampel Surabaya, 2006)
Â IjtihÃ¢d is the third legal source of Islam whose object is all things about whichthe Qurâan and the Sunnah are silent (mÃ¢ lÃ¢ naÅÅ Â fih). From the perspective of the UÅÃ»lal-Fiqh, there have been methods of ijtihÃ¢d put forward by the âUlama, which includeqiyÃ¢s, istiÅlÃ¢h, istishÃ¢b and âurf. These methods in the final analysis, should be based onwhat is commonly known as maqÃ¢Åid al-sharÃ®âah (human interest) when put into practice.When ijtihad is undertaken furthermore, two modes of thinking are normally born out ofmaqÃ¢Åid al-sharÃ®âah, one of which being âand this is the focus of our analysis- the taâlÃ®lÃ®mode of thinking. The taâlÃ®lÃ® mode of thinking is about discovering the reasons (âillah)behind certain religious rulings. It comes into existence as a result of the fact that thetexts of the Qurâan and the Sunnah always mention the reasons when issuing religiousrulings. And this has become the starting point of the mujtahids in resolving various legalissues that they face. They start by discovering first the reasons and then proceed to issuethe ruling. As far as the science of UÅÃ»l al-Fiqh is concerned, qiyÃ¢s and istihsÃ¢n belong tothis taâlÃ®lÃ® mode of thinking.